Comparisons in the Yakut and Tuvan epics: general and specific - Lvova, Sakhaya D. (The New Research of Tuva, 2021)
The article examines comparative structures in the texts of the Yakut olonkho “Kyys Debiliie” (as told by storyteller N. P. Burnashev), “Mighty Er Sogotokh” (by V. O. Karataev) and Tuvan epics “Khunan-Kara” (by Ch.-Kh. Ch. Oorzhak) and “Boktug-Kirish, Bora-Shelei” (by M. N. Oorzhak). The aim of the study is to discover both common and distinctive features in the use of comparisons and similes as a linguistic means of epic imagery based on the materials of the texts by Turkic peoples — Tuvans and Yakuts. Working within comparative method, the authors offer a classification of comparisons by thematic groups of objects and images, based on the systematization suggested by F. M. Selivanov in his study of comparisons in Russian bylinas.The method of continuous sampling from epic texts revealed 317 comparative constructions in Yakut and 199, in Tuvan texts. Quantitative indicators of the frequency of comparisons, as well as the percentage of their parallelization and thematic groups of simile components are calculated with the use of statistical analysis. It was found that the comparison is used more often in the Yakut olonkho than in the Tuvan ones. In both epics, comparisons are mainly formed as two-term parallelisms (more than 90%). Also determined are the concepts behind the main stable comparisons in the epics.The main attention in the work was paid to the composition of simile components, semantics, and function of images. Parallels between in associations and images in the similes were found. A comparative analysis of objects and images revealed largely archaic character of Tuvan similes. Their counterparts in the Yakut olonkho are distinguished by an abundance of biomorphic images, probably formed after they resettled in Yakutia. It has been discovered that similes in Tuvan texts are mainly used to exaggerate the number or size of an object, and in the Yakut olonkho the main function of comparisons is to convey a vivid visual image. In the materials of both epics, images are defined that express national specifics and reflect the geographical features of the habitat of the people who created this epic.
Keywords: Turkic epics; Yakut olonkho; Tuvan epics; Yakut folklore; Tuvan folklore; Yakuts; Tuvans; Yakut language; Tuvan language; speech means; epic imagery; simile; comparison image; object of compariso; object of comparison